The performance of cardio-biparietal ratio measured by 2D ultrasound in predicting fetal hemoglobin Bart disease during midpregnancy: A pilot study - Kuntharee Traisrisilp (2019)
© 2019 John Wiley & Sons, Ltd. Objective: The aim of this study was to assess the performance of cardio-biparietal ratio measured by real-time two-dimensional ultrasound in predicting hemoglobin (Hb) Bart disease among fetuses at risk. Method: This prospective diagnostic study recruited pregnancies at risk for Hb Bart disease at 17 to 22 weeks' gestation. Cardio-biparietal ratio and cardiothoracic ratio were measured before cordocentesis for Hb typing. The performance of the cardio-biparietal ratio and cardiothoracic ratio for identifying affected fetuses was evaluated. Results: Among 72 fetuses at risk, 31 were diagnosed as affected by Hb Bart disease. By using a cutoff 0.45, cardio-biparietal ratio had a sensitivity of 83.9%, specificity of 92.7%, positive predictive value of 89.7%, and negative predictive value of 88.4%, whereas cardiothoracic ratio using cutoff 0.5 had a sensitivity of 94.3%, specificity of 65.1%, positive predictive value of 68.8%, and negative predictive value of 93.3%. Conclusion: Cardio-biparietal ratio is a new sonomarker to predict Hb Bart disease among fetuses at risk. This sonomarker is relatively effective and may be useful in areas of high prevalence of alpha thalassemia disease, limited number of experts in prenatal ultrasound, and difficult access to prenatal diagnosis.